STRATEGI PEMBERDAYAAN KADER DENGAN APLIKASI “WILPIRANGAN” SEBAGAI MANAJEMEN POSYANDU INTEGRASI LAYANAN PRIMER MENUJU TRANSFORMASI KESEHATAN - Listyaningsih, Enik; Pratama, Antonius Yogi (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Primary Health Care (PHC) in Indonesia is not yet strong enough to solve the problems in Indonesia. The government is implementing a transformation of primary health care by implementing PHC through Integrasi Layanan Primer (ILP)/primary service integration. A WEB-based application called WILPIRANGAN (Web Integration of Primary Services RW 13 Malangan) is an application for a pilot project and serves as an evaluation material while preparing health cadres in performing Posyandu ILP services. The purpose of this research is to determine the effect of cadre empowerment through the use of web-based applications on the level of readiness of health cadres in performing ILP. The quasi-experimental or pre-experimental research method using a one group pretest and posttest group design approach was used with a sample of 40 health cadres who were distributed cadre readiness questionnaires. The results of respondent characteristics based on gender were mostly female, in the age category mostly Adults, and the most common occupation category was housewives, while the most common education category was High School. The Wilcoxon test showed a p-value= 0.001 (p-value <0,05). The conclusion is that there is an effect of technical guidance on the readiness of health cadres in using the "Welpirangan" application.